Effects of frequency and amount of stover mulching on the microbial community composition and structure in the endosphere and rhizosphere - Li, Haowen; Zou, Yawen; Song, Wenchen; Xin, Jiaxun; Gao, Jian (Frontiers in Microbiology, 2024)
Stover mulching, as a sustainable agricultural conservation practice, has been shown to effectively increase soil organic matter and enhance crop yields. The impact of stover mulching on soil microorganisms has been extensively studied. However, less attention has been given to endophytic and rhizospheric microorganisms that have closer relationships with crops. How do the quality and frequency of stover mulching affect the composition and structure of these endosphere and rhizosphere microbial communities? And what is their influence on critical indicators of soil health such as bacterial plant pathogen and Rhizobiales? These questions remain unresolved.Therefore, we investigated the responses of the microbial functional guilds in the endosphere and rhizosphere to maize stover mulching qualities (0, 33%, 67%, and total stover mulching every year) and frequencies (once every 3 years and twice every 3 years) under 10-year no-till management.Results showed significant correlations between Bacillales and Rhizobiales orders and soil SOC, NO3 -N, and NH4 + N; Hypocreales and Eurotiales orders were significantly correlated with soil NO3 - N, with the Aspergillus genus also showing a significant correlation with soil SOC. The frequency and quality of stover mulching had a significant effect on root and rhizospheric microbial communities, with the lowest relative abundance of bacterial plant pathogens and highest relative abundance of nitrogen-fixing bacteria such as Rhizobiales and Hypocreales observed under F1/3 and F2/3 conditions. The most complex structures in endosphere and rhizospheric microbial communities were found under Q33 and Q67 conditions, respectively. This research indicates that from a soil health perspective, low-frequency high-coverage stover mulching is beneficial for the composition of endosphere and rhizosphere microbial communities, while moderate coverage levels are conducive to more complex structures within these communities. This study holds significant ecological implications for agricultural production and crop protection.